Stability and nature of the volume collapse of ε-Fe2O3 under extreme conditions. Issue 1 (December 2018) - Sans, J.; Monteseguro, V.; Garbarino, G.; Gich, M.; Cerantola, V.; Cuartero, V.; Monte, M.; Irifune, T.; Muñoz, A.; Popescu, C.
Abstract Iron oxides are among the major constituents of the deep Earth's interior. Among them, the epsilon phase of Fe2 O3 is one of the less studied polymorphs and there is a lack of information about its structural, electronic and magnetic transformations at extreme conditions. Here we report the precise determination of its equation of state and a deep analysis of the evolution of the polyhedral units under compression, thanks to the agreement between our experiments andab-initio simulations. Our results indicate that this material, with remarkable magnetic properties, is stable at pressures up to 27 GPa. Above 27 GPa, a volume collapse has been observed and ascribed to a change of the local environment of the tetrahedrally coordinated iron towards an octahedral coordination, finding evidence for a different iron oxide polymorph. Iron oxides exist in a variety of polymorphs at different pressure and temperature conditions, displaying important magnetic properties, and are major constituents of the Earth's interior. Here the authors investigate the structural and electronic changes in the uncommon epsilon phase under compression to deep Mantle pressures.